Global and Local Buckling Behavior of Bracing Members with Slotted-in Web Openings - Firdausy, Ananda Insan; Lin, Chong-Jun (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
This study examines the global and local buckling behavior of segmented bracing members with slotted-in web openings, designed to reduce the demand on the mid-segment. The web-opening ratios were designed as 0.03 and 0.015, with one to three openings introduced along the steel wide-flange in the mid-segment. The results from the hysteresis loops indicated typical buckling-type brace behavior for most specimens, except for the specimen with a web-opening ratio of 0.015, which exhibited an unfavorable cyclic response with low stability. Specimens with a web-opening ratio of 0.03 demonstrated stable global buckling predominantly about the weak axis. In contrast, those with a ratio of 0.015 exhibited irregular global buckling that also involved strong-axis deformation. Similarly, specimens with a ratio of 0.015 exhibited irregular, deformed shapes and more severe local buckling around the web openings, whereas those with a ratio of 0.03 displayed more uniform deformation patterns. The specimen with two slotted-in web openings and a ratio of 0.03 achieved the highest buckling strength, as global buckling did not initiate at the web opening location, resulting in superior stability performance. Overall, specimens with a 0.03 web-opening ratio exhibited more favorable global and local buckling behavior, as well as higher buckling strength, compared to those with a ratio of 0.015.